tDCS over the left inferior frontal cortex improves speech production in aphasia - Marangolo, Paola (Frontiers in Human Neuroscience, 2013)
In this study, we investigated the combined effect of transcranial direct current stimulation (tDCS) and an intensive Conversational therapy treatment on discourse skills in twelve persons with chronic aphasia. Six short videoclips depicting everyday life contexts were prepared. Three videoclips were used to elicit spontaneous conversation during treatment. The remaining three were presented only before and after the therapy. Participants were prompted to talk about the contents of each videoclip while stimulated with tDCS (20 minutes, 1mA) over the left hemisphere in three conditions: anodic tDCS over the Broca’s area, anodic tDCS over the Wernicke’s area, and a sham condition. Each experimental condition was performed for ten consecutive daily sessions with 14 days of intersession interval. After stimulation over Broca’s area, the participants produced more Content Units, verbs and sentences than in the remaining two conditions. Importantly, this improvement was still detectable one month after the end of treatment and its effects were generalized also to the three videoclips that had been administered at the beginning and at the end of the therapy sessions. In conclusion, anodic tDCS applied over the left Broca’s area together with an intensive “Conversational Therapy” treatment improves informative speech in persons with chronic aphasia. We believe that positive tDCS effects may be further extended to other language domains, such as the recovery of speech production.